2019
DOI: 10.1177/1753193419866382
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the forearm interosseous membrane: a biomechanical study of three different techniques

Abstract: Reconstruction of the interosseous membrane has the potential to re-establish a normal loading pattern through the forearm and enhance stability after an Essex-Lopresti lesion. The aim of our study was to assess the capacity of three different techniques, which all use a regionally harvested autograft, to restore longitudinal stability. Simulation of the Essex-Lopresti lesion was done by excising the radial head and sectioning the interosseous membrane in seven cadaveric specimens. Each technique was used in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Cadaveric studies have tested different allografts for IOM reconstruction. 25 Pffaefle et al 21 used flexor carpis radialis (FCR) autograft and were able to restore resistance to axial loads with success, but tendon grafts lengthen over time because of plastic deformation of the tendon. Smith et al 26 reported one patient treated with flexor digitorum superficialis autograft with satisfactory results at four years’ follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric studies have tested different allografts for IOM reconstruction. 25 Pffaefle et al 21 used flexor carpis radialis (FCR) autograft and were able to restore resistance to axial loads with success, but tendon grafts lengthen over time because of plastic deformation of the tendon. Smith et al 26 reported one patient treated with flexor digitorum superficialis autograft with satisfactory results at four years’ follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, the overall stability of the forearm depends on the integrity of radioulnar articulations, encompassing the proximal radioulnar joint (PRUJ) and the distal radioulnar joint (DRUJ). These constructs are connected by the tough inelastic fibrous interosseous membrane (IOM) complex ( 26 ). IOM consists of five distinct components: the central band (CB); the accessory band (AB); the distal oblique bundle (DOB); the proximal oblique cord (POC), and the dorsal oblique cord ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…By far, reconstruction of the forearm interosseous membrane was a controversial topic. Some authors suggested enhancing the stability of the proximal radioulnar joint [37]. However, we considered that the tremendous clinical outcome could be achieved with a complete repair of the proximal radioulnar ligament and early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%